THE SALES PROMOTION ANALYSIS OF HIJAB PRODUCTS WYNABLE BRAND - Melani Putri; Santi Setiani; Mulyana Fauzi (Journal of Business Administration, 2022)
Currently selling fashion to facilitate transactions and save time, many use the internet. Wynable is a fashion product that uses internet marketing and the type of product offered is hijab. This article analyzes a business in the hijab industry that markets its products through online marketing and aims to understand digital marketing that is being used as well as product quality, prices and service at this store. The purpose of carrying out this promotion is to help businesses build brand awareness more effectively. Helping businesses establish communication with consumers. Through online promotional media, businesses are able to get input or suggestions directly from consumers. This research is a survey research using a qualitative approach, where data is obtained through observation of the online media used. Messages conveyed in the form of marketing, as well as conducting special interviews with the owner or owner of Wynable by chat or question and answer. The conclusion from this discussion means that the marketing strategy used in Wynable uses only one marketing method, namely the online marketing approach. And also the product quality, price and service are quite good.